2015
DOI: 10.3945/jn.115.215392
|View full text |Cite
|
Sign up to set email alerts
|

A Single Meal Containing Raw, Crushed Garlic Influences Expression of Immunity- and Cancer-Related Genes in Whole Blood of Humans

Abstract: These data indicate that the bioactivity of garlic is multifaceted and includes activation of genes related to immunity, apoptosis, and xenobiotic metabolism in humans and Mono Mac 6 cells. This trial is registered at clinicaltrials.gov as NCT01293591.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 69 publications
(67 reference statements)
0
25
0
Order By: Relevance
“…An immune enhancing effect of garlic was also confirmed in a randomized clinical trial with 17 volunteers who had a garlic-free or garlic-containing meal for 10 days. The trial showed that garlic can upregulate immune response genes and activate apoptosis and the xenobiotic metabolism in people who regularly consume garlic containing meals ( Charron et al, 2015 ). The anti-inflammatory and immunomodulatory potential of garlic was also subject to a most recent publication indicating that garlic may be beneficial as a preventive measure in the current COVID-19 pandemic ( Donma & Donma, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An immune enhancing effect of garlic was also confirmed in a randomized clinical trial with 17 volunteers who had a garlic-free or garlic-containing meal for 10 days. The trial showed that garlic can upregulate immune response genes and activate apoptosis and the xenobiotic metabolism in people who regularly consume garlic containing meals ( Charron et al, 2015 ). The anti-inflammatory and immunomodulatory potential of garlic was also subject to a most recent publication indicating that garlic may be beneficial as a preventive measure in the current COVID-19 pandemic ( Donma & Donma, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Garlic are immune modulators and reports suggest dietary meal containing garlic (raw or crushed) can influence the expression of immunity in humans ( Abdullah, 2000 ; ( Charron et al, 2015 ). A recent clinical trial has shown that diet supplemented with aged garlic extract (AGE) can modulate the inflammation and immunity of adults with obesity ( Xu et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous mechanisms have been recommended to explain the chemo-preventive effects of garlic, including the inhibition of DNA adduct formation, the inhibition of mutagenesis by blocking metabolism, through its free-radical scavenging, or by decreasing cell proliferation and tumor growth [ 74 ]. In this context, Charron et al [ 76 ] performed a clinical trial on gene expression related to immunity, apoptosis, and xenobiotic metabolism in humans, after consumption of 5 g raw, crushed garlic daily for 10 days. A single meal containing raw crushed garlic activated the expression of seven genes, such as activating protein with immunoreceptor tyrosine-based activation motif 1, aryl hydrocarbon receptor nuclear translocator, aryl hydrocarbon receptor, hypoxia-inducible factor 1α, c-Jun, nuclear factor of activated T cells, oncostatin M and V-rel avian reticuloendotheliosis viral oncogene homolog in blood of healthy volunteers, thus inhibiting tumorigenesis.…”
Section: Clinical Trials On Garlicmentioning
confidence: 99%
“…The allyl mercaptan with the best histone deacetylase inhibitor from garlic revealed its anticancer mechanisms [ 61 ]; however Z-ajoene from garlic can be treated the glioblastoma by targeting its cancer stem cells [ 62 ]. Garlic intake is negatively associated with the cancer and cardiovascular disease, based on activation of genes with immunity, apoptosis, and xenobiotic metabolism [ 110 ].…”
Section: Chronic Disease Prevention Of Allium Gmentioning
confidence: 99%